Evaluation of therapeutic response of methotrexate and calcipotriol combination compared with methotrexate alone in plaque psoriasis - Deepthi Vasanthada; Vasanth Kumar PM; Krishna Rao Pasagadagula; Ramesh Tatapudi; Ramesh Malothu (Our Dermatology Online, 2014)
Introduction: Psoriasis is a common chronic, non-contagious, immune mediated disease. Plaque psoriasis is characterized by thick, white, silvery or red patches on the skin. Plaque psoriasis mainly affects scalp, and palms of hands and soles of feet. T-cells are a type of immune system cells which protect the body from foreign substances. But during psoriasis T-cells activated at a great rate than normal, in turn release of cytokines increases as a result skin cells growing too quickly, moving to the surface to the skin and appear on the skin as dead cells. Materials and Methods: Plaque psoriasis is common form of psoriasis, which mainly affects palms of hands and soles of feet and scalp. Out of 76 patients with plaque psoriasis we selected 50 patients based on PASI scores. Within the 50 patients, 32 patients with Palmoplantar psoriasis and 18 patients with scalp psoriasis. All 50 patients were subjected to randomized control trail, so each type of psoriasis is divided into two groups i.e. A and B. All A group patients were treated with MTX, whereas all B group patients were treated with combination of MTX and Calcipotriol. All necessary investigations like complete blood count, liver enzyme,creatinine, urea, alkaline phosphate, PASI were measured at 0, 2,4 6,8 weeks interval. Results: We observed that, a significant reduction in PASI is observed with combination of MTX and Calcipotriol as compared to Methotrexate alone. Conclusion: From the above study we concluded that, combination of MTX and Calcipotriolis more effective than MTX alone in plaque psoriasis.